2002
DOI: 10.1023/a:1014471500757
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Adult T-cell leukemia/lymphoma (ATL) is a distinct clinicopathological entity, i.e., peripheral T-lymphocytic malignancy caused by human T-lymphotropic virus type I (HTLV-1) with diverse clinical features. High frequency of genetic instability (GIN) in both aggressive and indolent ATL was detected by comparative genomic hybridization (CGH). Among GIN, chromosomal instability, i.e., ancuploidy, in indolent ATL was as frequent but less complex and dynamic as compared to those in aggressive ATL. Some of the CGH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The primary leukemic cells analyzed in this study harbored genetic aberrations similar to aberrations previously reported in the literature and included frequent chromosomal gains of chromosomal regions 3p, 7q, 1q, 2q, 3q, 8p, 8q, 9q, 18q, and 19p, in addition to losses at chromosomal regions 6q, 2q, 4q, 5q, 10p, 10q, 12p, 18p, and chromosome 13 [47,48]. Analyses of correlation between chromosomal changes and alteration in gene expression of chromosomes located in the chromosomal aberration regions demonstrated relatively poor correlation, similar to our observations in transformed follicular lymphoma specimens [49].…”
Section: Discussionmentioning
confidence: 65%
“…The primary leukemic cells analyzed in this study harbored genetic aberrations similar to aberrations previously reported in the literature and included frequent chromosomal gains of chromosomal regions 3p, 7q, 1q, 2q, 3q, 8p, 8q, 9q, 18q, and 19p, in addition to losses at chromosomal regions 6q, 2q, 4q, 5q, 10p, 10q, 12p, 18p, and chromosome 13 [47,48]. Analyses of correlation between chromosomal changes and alteration in gene expression of chromosomes located in the chromosomal aberration regions demonstrated relatively poor correlation, similar to our observations in transformed follicular lymphoma specimens [49].…”
Section: Discussionmentioning
confidence: 65%